2014
DOI: 10.1038/pr.2014.117
|View full text |Cite
|
Sign up to set email alerts
|

Combination of intrauterine growth restriction and a high-fat diet impairs cholesterol elimination in rats

Abstract: Background: Intrauterine growth restriction (IUGR) increases the risk of adult-onset hypercholesterolemia. High-fat diet (HFD) consumption potentiates IUGR-induced increased cholesterol. Cholesterol is converted to bile acids by Cyp7a1 in preparation for excretion. We hypothesized that IUGR rats fed a HFD will have increased cholesterol, decreased Cyp7a1 protein levels, and decreased bile acids compared to control rats fed a HFD. Methods: At day 21, IUGR and control pups were placed on one of three diets: a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…In this study, we found that the increase in the serotonin and TPH1 levels was accompanied by an increase in CA and DCA levels in the HFD-fed rats. These results were consistent with previous results, which suggested that a high-fat diet could result in the accumulation of CA and secondary bile acids [ 41 , 42 ]. A high-fat diet could increase the levels of cholesterol in the liver, which is required for the synthesis of bile acids [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we found that the increase in the serotonin and TPH1 levels was accompanied by an increase in CA and DCA levels in the HFD-fed rats. These results were consistent with previous results, which suggested that a high-fat diet could result in the accumulation of CA and secondary bile acids [ 41 , 42 ]. A high-fat diet could increase the levels of cholesterol in the liver, which is required for the synthesis of bile acids [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…After FMT for only two weeks, the TPH1 expression, and the concentration of serotonin in the small intestinal tissues reduced. Furthermore, our results showed that FMT was also able to reduce the DCA and CA concentration of the intestinal contents in the HFD-fed rats, which may be the factors that could downregulate TPH1 expression [ 38 , 42 ]. This indicated that FMT could impact the biotransformation of the bile acids, and this may have a close association with the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies suggest that IUGR predisposes individuals to hypercholesterolemia susceptibility compared with their normally grown peers (3,23,53). We have shown that IUGR animals challenged with a postnatal HFD have increased cholesterol compared with control animals with a HFD alone (71). Additionally, maternal obesity and HFD consumption during pregnancy increase the risk of placental insufficiency and independently program CVD in the offspring (24,38,49).…”
Section: New and Noteworthymentioning
confidence: 96%
“…NoxO1 is believed to be a regulatory subunit mainly for the NOX1 [81], but is not necessary for NOX1 activation since its homologue, p47 phox , can also activate NOX1. In addition, it is recognized that NoxO1 activates NOX3 and NOX2 [82], but less efficiently than p47 phox activates NOX2 [83]. Therefore, differential enzyme activity of other NOX isoforms, like NOX3 and NOX2, may contribute to different angiogenic phenotypes seen in Nox1 −/− and NoxO1 −/− mice.…”
Section: Nadph Oxidase (Nox) In Angiogenesismentioning
confidence: 99%